Redescription of Brazilichthys macrognathus Cox & Hutchinson, 1991 (Actinopterygii) and a new coelacanth for the Permian (Cisuralian) Pedra de Fogo Formation, Brazil - Figueroa, Rodrigo Tinoco (2019)
The Pedra de Fogo Formation represents the Lower Permian, Cisuralian, interval of the Parnaíba Basin, extending through the states of Piauí, Maranhão and Tocantíns. Despite its considerably diverse vertebrate fauna, there are few studies regarding its bony fishes. Most of the studies focus on the chondrichthyan and tetrapod faunas. Several bony fish groups are known for this formation, including actinopterygians, lungfishes and coelacanths, normaly based on fragmentary and poorly preserved specimens. The only partially articulated osteichthyan formally described is Brazilichthys macrognathus, but only superficially described. The osteichthyans from the upper Paleozoic are poorly known for western Gondwana, being few species described on the basis of articulated specimens. This leads to the negligence of these South American taxa on large phylogenetic analysis for Actinopterygii and Sarcopterygii. Here I redescribe Brazilichths, as well as describing a new coelacanth genus from the same locality, using new data of microcomputed tomography, as well as their phylogenetic position based on parsimony and Bayesian analyses. The data presented herein highlights the fossiliferous potential of the Pedra de Fogo Formation, due to the presence of well-preserved and partially articulated three-dimensional specimens. In addition, the phylogenetic position of the two taxa indicate a mixture of derived and primitive traits for the Permian, suggesting that novel evolutionary traits were emerging during the Permian. This reinforces the need of detailed studies regarding the South American Paleozoic paleoichthyofauna, which could shead light on important questions about the diversification and evolution of bony fishes during the late Paleozoic